Ascending to descending aortic prosthesis with reimplantation of brachiocephalic vessels in aneurysm of the arch and descending aorta for hypoplasia of the arch and coarctation of the aorta - B.M. Todurov; O.V. Zelenchuk; S.M. Sudakevych; A.Yu. Shkandala; N.S. Gnoyanko (Кардіохірургія та інтервенційна кардіологія)
Thoracic aortic aneurysm is one of the most serious pathologies of cardiovascular surgery. Occurrence of an aneurysm in the proximal or distal part of the aortic arch is a recognized complication of uncorrected aortic coarctation and is associated with a significant risk of aortic rupture. The article presents a case of surgical treatment of a 36-year-old woman with untreated hypoplasia of the arch and coarctation of the aorta. Our experience shows that the operation of anatomical ascendo-descendoaortic prosthetics is a useful and safe method of surgery in patients with aortic arch aneurysms at high risk of endovascular or hybrid types of interventions